Implementation of Strengthening the Profile of Pancasila Students in Indonesian Learning Containing Cultural Values of Wayang Stories in Elementary Schools - Nuryanti, Nuryanti; Slamet, Sty; Daryanto, Joko (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation of Indonesian language learning embedded with local cultural values from wayang stories to strengthen the dimensions of the Pancasila Student Profile at the elementary school level. Methodology: This study used a qualitative descriptive approach with a bounded case study design. Data were collected using interview instruments validated by education experts, classroom observations, and documentation analysis. The data were analyzed using Miles and Huberman's interactive model to identify planning, implementation, challenges, and perceptions in cultural-based learning. Main Findings: The study found that integrating wayang stories into Indonesian language learning increased students' engagement and understanding of character values such as honesty, responsibility, and cooperation. Teachers showed creativity in designing learning activities but still encountered challenges in evaluation tools and time constraints. Localized story adaptation and collaboration with cultural communities became effective strategies to overcome these barriers. Novelty/Originality of this study: This study introduces a structured learning model that combines language learning with cultural narratives to reinforce character education aligned with the Pancasila Student Profile. It contributes to the development of culturally responsive pedagogy and offers practical solutions for embedding local wisdom into the national curriculum